What Internal Factors Influence the Capacity Expansion Decisions of Family Businesses Regarding the Recycling of Animal Waste? - Model Testing Research from the Meat Industry - Kinga Nemes; Márta Konczosné Szombathelyi; Péter Kovács (Chemical Engineering Transactions)
A significant amount of animal waste is generated in the meat industry, and this is no different in the case of family businesses in the meat industry, be it slaughterhouses, meat processors or poultry farms. Animal waste is not always waste. Some parts of it can be recycled. In the course of their research, the authors tested their previously developed model with an online survey of 45 family businesses in the meat industry and with in-depth interviews analysed with the help of artificial intelligence. The aim of the research is to assess which internal factors influence the decision of family businesses in the meat industry to expand the capacity required for the recycling of animal waste. The research verified the model and provided useful, practical examples for the utilisation of animal waste.